Developing a measure of polypharmacy appropriateness in primary care: systematic review and expert consensus study - Burt, Jenni; Elmore, Natasha; Campbell, Stephen. M.; Rodgers, Sarah; Avery, Anthony J.; Payne, Rupert A. (BioMed Central, 2018)
Background: Polypharmacy is an increasing challenge for primary care. Although sometimes clinically justified, polypharmacy can be inappropriate, leading to undesirable outcomes. Optimising care for polypharmacy necessitates effective targeting and monitoring of interventions. This requires a valid, reliable measure of polypharmacy, relevant for all patients, that considers clinical appropriateness and generic prescribing issues applicable across all medications. Whilst there are several existing measures of potentially inappropriate prescribing, these are not specifically designed with polypharmacy in mind, can require extensive clinical input to complete, and often cover a limited number of drugs. The aim of this study was to identify what experts consider to be the key elements of a measure of prescribing appropriateness, in the context of polypharmacy.